Analysis of the Time-frequency Connectedness between Gold Prices, Oil Prices and Hungarian Financial Markets - Hung, Ngo Thai (International Journal of Energy Economics and Policy, 2020)
We study the time-frequency connectedness between the global commodities markets (crude oil and gold) and Hungary’s equity markets (stock and exchange rate) by using the multivariate generalized autoregressive conditional heteroskedasticity dynamic conditional correlation DCC-GARCH model alongside with the wavelet coherence analysis. Results of this paper highlight the long-term time-varying intercorrelations between the global commodities markets and Hungarian financial markets. Additionally, the estimations of wavelet coherence indicate that the commodities markets have a significant impact on the Hungarian financial markets in the short term, but stock and exchange markets influence crude oil and gold markets in the long run. Our empirical results shed light on the commodity-finance sectors connectedness, which is able to help investors minimize risks to build discretionary portfolios. Keywords: oil price, gold price, stock market, exchange rate, DCC-GARCH, wavelet technique, Hungary. JEL Classifications: G10; G11; C32; E44 DOI: https://doi.org/10.32479/ijeep.9230